2010
DOI: 10.1590/s1808-86942010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalências das mutações 35delG/GJB2 e del (GJB6-D13S1830) em portadores de surdez não-sindrômica na população do Espírito Santo - Brasil

Abstract: Master's degree, professor at the Sao Pedro Integrated Faculties (Faculdades Integradas São Pedro), AEV/FAESA and doctoral student in biotechnology, RENORBIO/UFES. 2 Graduated in biological sciences, researcher. 3 Graduated in biological sciences, researcher. 4 Graduated in biological sciences, researcher. 5 Doctoral degree, research and outreach coordinator at the Sao Pedro Integrated Faculties, AEV/FAESA. Sao Pedro Integrated Faculties (AEV/FAESA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…35delG mutation takes place by deletion of one guanine (G) in a run of six guanines extending from position 30 to position 35 in the GJB2 gene causing a frameshift of the coding sequence leading to premature chain termination at the twelfth amino acid [9]. Other studies in small groups found that this variant is responsible for nonsyndromic recessive deafness in a Muslim-Israeli village in the lower Galilee [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35delG mutation takes place by deletion of one guanine (G) in a run of six guanines extending from position 30 to position 35 in the GJB2 gene causing a frameshift of the coding sequence leading to premature chain termination at the twelfth amino acid [9]. Other studies in small groups found that this variant is responsible for nonsyndromic recessive deafness in a Muslim-Israeli village in the lower Galilee [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is found in more than half of all GJB2 mutations discovered so far [9]. This mutation creates a frameshift resulting in a short nonfunctional truncated form of the protein [10].…”
Section: Introductionmentioning
confidence: 99%
“…In Argentina it was found that the c.35delG mutation is the most frequent cause of NSHL, with a frequency of 1.5% in heterozygotes, a little lower than the observed among the European populations [48,[94][95][96]. In Brazil, mutations in the GJB2 gene are the leading cause of deafness in autosomal recessive inheritance, and the c.35delG mutation is the most common variant in many ethnic groups [78], where 1 in 51 Caucasians (1.9%) carries the c.35delG mutation, aligning closely with the rates observed in most European populations [97]. Studies form several regions of Brazil indicates that the c.35delG mutation is very common, with prevalence that can range from 0.97%, in neonates in the state of Sao Paulo (identified in 1 out of 103 neonates) [98], to 12.4% overall, where this mutation was identified in 23% of familial cases and 6.2% of sporadic cases [99].…”
Section: Current Situation In Latin Americamentioning
confidence: 96%
“…[76,77]. In Brazil, by 2010, the incidence of hearing impairment was approximately 4 cases per 1000 births [78]. Environmental factors contribute to 80% of these cases, while genetic factors are responsible for the remaining 20% [79].…”
Section: Current Situation In Latin Americamentioning
confidence: 99%